Papel dos conselhos de direitos da criança e do adolescente na política de convivência familiar e comunitária - Albuquerque, Leonam Amitaf Ferreira Pinto de (2023)
The objective of this research is to analyze the role of child rights councils in the policy of the right to live in a family and community environment through the actions of social agents. This is a qualitative and exploratory work, divided into three studies: the first is a systematic literature review, the second is a doc umental analysis, and the third is a discussion group. Data were analyzed respectively using PRISMA, analytical treatment and Content Analysis. In the systematic review, was observed a significant amount of roles attributed to agents by the recovered works . In the documental analysis, the plans foresaw the division of responsibilities, the family support and the policy control, while the minutes prioritized the discussion on institutional reception and adoptive family In the discussion group, the participa nts talked about the arrangements, mobilizations and strategies employed by the agents to execute the policy. The role of the child rights councils in the policy of the right to live in a family environment is to implement policies, exercise control and build alliances. These attributions are crossed by the limits of social policy in capitalism, the emergence of forms of social organization, the disputes and negotiations between groups and the reduction of clas s struggle to individual demands.